Elimination of Cassava Mosaic Disease through Meristem Culture and Field Evaluation for Yield Loss Assessment in Cassava Genotypes - Deepthi, D C; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2016)
The presence of Sri Lankan cassava mosaic virus (SLCMV) and Indian cassava mosaic virus (ICMV) and other cassava mosaic viruses which cause cassava mosaic disease is a major threat to cassava production worldwide. Therefore it is highly advantageous to use virus free cuttings for multiplication and cultivation. Here we report meristem culture for cleaning of five different cassava cultivars infected with SLCMV. Polymerase chain reaction (PCR) was employed to index meristem derived plants using specific primers. The meristem derived plantlets were free of symptoms and further confirmed the absence of virus through PCR using virus specific primers. Meristem derived plants were included in field study to determine the effect of SLCMV infection in yield. Meristem derived virus free planting materials increases yield but such advantage soon lost due to rapid re-infection with virus on field grown plants through efficient whitefly transmission.